The Marginalization of Faculty and the Quantification of Educational Policy: Lessons from My Many Years on Faculty Senates - Segal, Howard (Maine Policy Review, 2019)
Howard Segal shares conclusions about higher education and policy that apply to public colleges and universities across the country.